Schizophrenia: A Very Short Introduction - Frith, Christopher and Johnstone, Eve (New York Oxford University Press, 2003)
The schizophrenic patient presented to the public in sensational press reports and lurid films bears little resemblance to reality of the illness. This book describes what schizophrenia is really like, how the illness progresses, and the treatments that have been applied. It also summarizes the most up-to-date knowledge available about the biological bases of this disorder. Finally it attempts to give some idea of what it is like to have schizophrenia and what this disorder tells us about the relationship between mind and brain.
Includes Index and Illustrations.
Keywords: Schizophrenia